PENGARUH SENAM A-PIK (ANTI PIKUN) TERHADAP KUALITAS HIDUP PADA ORANG DENGAN DEMENSIA - Charish Rachmatullah, - (2020)
Perceptions of quality of life are viewed globally so that the quality of life is assessed to further develop, including the elderly. Quality of life is an important concept to serve as a criterion that evaluates penetration in health services. The elderly have several problems that cannot be avoided, this shows that the elderly who often do physical activity are able to maintain healthy bodily functions longer than the elderly who remain silent. Physical activity is actually one that cannot be separated from everyday life. One sign of health is one's ability to perform physical activities such as standing, walking and working. Often due to various reasons, someone is lazy to move and carry out their daily activities. Even though doing activities make it important for life in maintaining health. People who carry out physical activity and have a high level of activity are declared to have good health and quality of life. Therefore, the aim of this study was to examine the effect of A-Pik exercise on quality of life in people with dementia. In this research, using experimental research in the form of pre-experimental design. Participants involved in this study were people with dementia who came from Cibeunying Kidul sub-district, Padasuka Village and managed by a POSBINDU (Integrated Assistance Post) named Tanjung and had dementia. The population in this study amounted to 69 people with a sample of 22 people. Based on the research results, the effect of A-Pik Exercise on Quality of Life has been obtained at p (0.000) <0.05, this shows that there is a significant difference in the quality of life of people with dementia.